2005
DOI: 10.1007/s00203-005-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Production and partial characterization of extracellular proteinases from Streptomyces malaysiensis, isolated from a Brazilian cerrado soil

Abstract: Streptomyces malaysiensis AMT-3, isolated from a Brazilian cerrado soil, showed proteolytic activities detected by gelatin-sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The optimum proteinase production was obtained when using 2.5% wheat bran and 0.1% yeast extract in the culture medium, after 5 days incubation at 30 degrees C. The enzymatic complex degraded gelatin optimally at pH 7.0, and under these conditions eight proteolytic bands (four serine-proteinases and four metaloproteinases), ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…For an optimal enzyme production, it is also necessary to reach a good mix of the culture broth because agitation produces a dispersion of air in the culture medium, homogenizes the temperature and the pH, and improves transference rate of nutrients (Markl & Bronnenmeier, 1985). In this respect, similar results were reported by Nascimento et al (2005) for S. malaysiensis AMT-3;De Azeredo et al (2006a, b) for Streptomyces sp. 594; Ramesh et al (2009) for S. fungicidicus MML 1614 and Dixit & Pant (2000) for Nocardiopsis sp.…”
Section: Effect Of Aeration On Alkaline Protease Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…For an optimal enzyme production, it is also necessary to reach a good mix of the culture broth because agitation produces a dispersion of air in the culture medium, homogenizes the temperature and the pH, and improves transference rate of nutrients (Markl & Bronnenmeier, 1985). In this respect, similar results were reported by Nascimento et al (2005) for S. malaysiensis AMT-3;De Azeredo et al (2006a, b) for Streptomyces sp. 594; Ramesh et al (2009) for S. fungicidicus MML 1614 and Dixit & Pant (2000) for Nocardiopsis sp.…”
Section: Effect Of Aeration On Alkaline Protease Productionsupporting
confidence: 90%
“…Peptone, 4; Glucose, 10; K2HPO4, 0.5; MgSO4.7H2O, 0.5; NaCl, 0.5; CaCl2, 0.5; Distilled water, 1000 ml; pH, 9 (Ramesh et al, 2009). 5 KH2PO4, 1.5; K2HPO4 , 9.0; MgSO4.7H2O, 0.2; CaCl2, 0.05; MnSO4, 0.01; ZnSO4.7H2O, 0.001;Yeast extract , 0.01; Wheat bran, 0.25; Distilled water, 1000 ml; pH, 9 (Nascimento et al, 2005).…”
mentioning
confidence: 99%
“…da Silva (2012) described 2152 complete or partial isolates of actinobacteria from Cerrado soil samples that differed phenotypically from previously described members of this phylum. Some actinobacteria isolated from Cerrado soil samples exhibit chitinolytic and proteinase activities (Petinate et al 1997;Gomes et al 2000;Nascimento et al 2005). Other studies have also described the isolation of novel actinomycetes and acidobacterial species from Cerrado soil (Albuquerque de Barros et al 2003;.…”
Section: Microorganisms In Ecosystem Function: Taxa Vs Functionmentioning
confidence: 94%
“…Previous studies have reported high numbers of Actinobacteria in Cerrado soils (Nascimento et al, 2005;Suela Silva et al, 2013; de Sales et al, 2017;Vieira et al, 2018;Vargas Hoyos et al, 2019). These soils are acidic and have a low availability of macronutrients (nitrogen, P, potassium, calcium, magnesium, and sulfur) and micronutrients (boron, copper, molybdenum, and zinc) (Cruz Ruggiero et al, 2002;Oliveira and Marquis, 2002;Genuário et al, 2019).…”
Section: Potential Of Phosphorus Mobilizationmentioning
confidence: 99%